2012
DOI: 10.1063/1.4739421
|View full text |Cite
|
Sign up to set email alerts
|

Restricted dynamics of water around a protein–carbohydrate complex: Computer simulation studies

Abstract: Water-mediated protein-carbohydrate interaction is a complex phenomenon responsible for different biological processes in cellular environment. One of the unexplored but important issues in this area is the role played by water during the recognition process and also in controlling the microscopic properties of the complex. In this study, we have carried out atomistic molecular dynamics simulations of a protein-carbohydrate complex formed between the hyaluronan binding domain of the murine Cd44 protein and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…It has been shown that heterogeneity in the dynamics of water interactions is coupled to differential time scales of hydrogen bond formation and breaking (42). Using a wavelength-selective fluorescence approach (REES), we showed that entry to the inactivated state is associated with the presence of restricted/bound water molecules in the outer vestibule of KcsA (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…It has been shown that heterogeneity in the dynamics of water interactions is coupled to differential time scales of hydrogen bond formation and breaking (42). Using a wavelength-selective fluorescence approach (REES), we showed that entry to the inactivated state is associated with the presence of restricted/bound water molecules in the outer vestibule of KcsA (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Given these differences, further investigation is warranted to achieve a comprehensive consistent view. Finally, while outside the scope of this review, there have been substantial efforts using MD simulations to understand the importance of water molecules and of biomolecular conformational entropy changes in HABD binding with HA (52, 53). Findings from these simulations that can inform development of small-molecule modulators of CD44 function include reduced translational and rotational freedom of water molecules in contact with HABD and HA, and loss of HA flexibility associated with binding to HABD.…”
Section: Resultsmentioning
confidence: 99%
“…(4951) This article reviews the contribution MD simulations have made toward developing answers to these questions. We note that others have also recently applied MD simulation to the study of CD44 HABD, with topics including conformational flexibility and the microscopic structure and dynamics of water surrounding HABD (52, 53), and the mechanism and thermodynamics of the ordered to partially disordered transition (54). …”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][32][33][34][35][36][37][38][39][40][41][42] Especially, the existence of polar groups at the interface can dominate the formation and breaking of interfacial HBs. 33,36,37,40 Balasubramanian and Bagchi 34 have shown that the HB lifetime between water molecules and the polar head groups (cesium pentadecafluorooctanoate) at a micelle surface is found to be much longer than that of water molecules themselves.…”
Section: Introductionmentioning
confidence: 99%